2005
DOI: 10.1007/bf03354659
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study evaluating a minimal contact telephone and mail weight management intervention for primary care patients

Abstract: This pilot study suggests that minimal interventions may be a method to reach populations that do not have access to more intensive treatments for weight management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…[13][14][15] In particular, weight loss was greater than what was observed in a study that used a very similar treatment structure, but did not include a home telemonitoring scale. 16 Also, the effect size in this trial was higher as compared to these other studies.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…[13][14][15] In particular, weight loss was greater than what was observed in a study that used a very similar treatment structure, but did not include a home telemonitoring scale. 16 Also, the effect size in this trial was higher as compared to these other studies.…”
Section: Discussionmentioning
confidence: 80%
“…Early empirical evidence in this area suggested that telephone-based counseling is a moderately effective treatment approach as compared to minimal or no contact interventions. 11,12 More recent trials [13][14][15][16] have substantiated that telephone-based counseling does produce weight loss and that there is at least moderate market demand for such services. 17 Another weight loss strategy that has received more attention lately is regular self-monitoring of weight.…”
mentioning
confidence: 99%
“…• Follow-up less than six months [36][37][38][39] • Studies were solely reports of study design and rationale [40][41][42][43][44][45][46][47][48][49] • Drug no longer available 22 50 • No primary care provider or team member involved [51][52][53][54][55][56][57][58] • Design was non-randomized [59][60][61] • Previously included in a systematic review 23-31 34 62-65 • Study was a systematic review 19 21 66 • Study included non-overweight people. 67 After these exclusions, six publications representing four studies were reviewed in detail and data abstracted (table).…”
Section: Subsequent Evidencementioning
confidence: 99%
“…Numerous interventions have been employed in the last two decades to help overweight children reduce their fat mass and maintain a healthy weight (Baranowski, Cullen, Nicklas, Thompson, & Baranowski, 2002; Caballero et al., 2003). Interventions using postal mail have had some success in promoting physical activity and improving dietary intake in adults and children (Boutelle, Dubbert, & Vander Weg, 2005; Davis & James, 2007; Sherwood et al., 2006). Printed educational materials are frequently used in primary care and community settings.…”
mentioning
confidence: 99%